A study on ultrasonic assisted extraction and formulate natural hair shampoo from sapindus emarginatus - Nurul Ain, Hamdan Abd. Khalek (2012)
Hair shampoo is a personal care product that can removes dirt,skin particle,and sebum from hair skin.Mostly of hair shampoo consist of dangerous ingredient such as Sodium Laureth Sulfate which it produces skin and hair damages, including cracking and severe inflammation of tissue.Thus, Sapindus emarginatus will be used as main ingredient for a new formulation of hair shampoo.This herb material contains an active compound known as saponin which can replace the dangerous compound in hair shampoo.The objective of this research is to extract saponin from Sapindus emarginatus using ultrasound assisted extraction in order to formulate natural hair shampoo.The yields of saponin was measured by HPLC by study the effect of different size particle, sonication time and temperature.Based on result,the maximum amount of saponin extracted obtained at size particle 315 µm,sonication time at 60 minutes and temperature at 60°C .The herbal extract was mix with other ingredients such as Methyl paraben and EDTA to form of a new formulation. The shampoo was tested using pH test.The extraction rate constant,k of saponin decreased with increasing temperature and sonication time,and the k values between range 0.1091 to 0.430. Thus,the saponin with higher concentration is used as main ingredient in order to formulate natural hair shampoo.